Adsorption of alkanes on stoichiometric and oxygen-rich RuO2(110). Issue 32 (1st August 2016) - Li, Tao; Kim, Minkyu; Rai, Rahul; Liang, Zhu; Asthagiri, Aravind; Weaver, Jason F.
Abstract : Alkanes form strongly-bound σ-complexes on RuO2 (110) and change configurations in the presence of co-adsorbed oxygen atoms. Abstract : We investigated the molecular adsorption of methane, ethane, propane and n -butane on stoichiometric and oxygen-rich RuO2 (110) surfaces using temperature-programmed desorption (TPD) and dispersion-corrected density functional theory (DFT-D3) calculations. We find that each alkane adsorbs strongly on the coordinatively-unsaturated Ru (Rucus ) atoms of s-RuO2 (110), with desorption from this state producing a well-defined TPD peak at low alkane coverage. As the coverage increases, we find that alkanes first form a compressed layer on the Rucus atoms and subsequently adsorb on the bridging O atoms of the surface until the monolayer saturates. DFT-D3 calculations predict that methane preferentially adsorbs on top of a Rucus atom and that the C2 to C4 alkanes preferentially adopt bidentate configurations in which each molecule aligns parallel to the Rucus atom row and datively bonds to neighboring Rucus atoms. DFT-D3 predicts binding energies that agree quantitatively with our experimental estimates for alkane σ-complexes on RuO2 (110). We find that oxygen atoms adsorbed on top of Rucus atoms (Oot atoms) stabilize the adsorbed alkane complexes that bind in a given configuration, while also blocking the sites needed for σ-complex formation. This site blocking causes the coverage of the most stable, bidentate alkane complexes to decrease sharply with increasing Oot coverage. Concurrently, we find that a new peak develops in the C2 to C4 alkane TPD spectra with increasing Oot coverage, and that the desorption yield in this TPD feature passes through a maximum at Oot coverages between ∼50% and 60%. We present evidence that the new TPD peak arises from C2 to C4 alkanes that adsorb in upright, monodentate configurations on stranded Rucus sites located within the Oot layer.